2022
DOI: 10.1192/bjo.2022.27
|View full text |Cite
|
Sign up to set email alerts
|

Intervening to prevent suicide at railway locations: findings from a qualitative study with front-line staff and rail commuters

Abstract: Background For every suicide on the British railway network, at least six potential attempts are interrupted by front-line staff or rail commuters. However, the factors that maximise or hinder the likelihood and effectiveness of such interventions are poorly understood. Aims The aim of the current study was to shed light on the experience of intervening to prevent a suicide at a railway location, including how and why people intervene, and their feelings and reflections in the aftermath.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…We recruited an opportunity sample of participants for interview from among those who had taken part in a second online survey in 2019. 13 Participants were aged 18 years or over and had stated in the survey that they had felt suicidal at a road or bridge location. We contacted 41 people meeting these criteria who had not previously been interviewed for a different follow-up study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recruited an opportunity sample of participants for interview from among those who had taken part in a second online survey in 2019. 13 Participants were aged 18 years or over and had stated in the survey that they had felt suicidal at a road or bridge location. We contacted 41 people meeting these criteria who had not previously been interviewed for a different follow-up study.…”
Section: Methodsmentioning
confidence: 99%
“…Interview participants were recruited following a second survey, also funded by Network Rail on behalf of the rail industry. 13 We thank Dafni Katsampa for her assistance with this project. Finally, we are grateful to Jo Porter for transcribing the interviews.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…In Uk, indeed, every year, around 6000 suicides are recorded (Katsampa, 2022). The first way to control and prevent these fatal accidents is modern Rail Network Surveillance; a case study on implementing an automatic sensor that can evaluate possible accidents has reported very good results .…”
Section: Platform Accidents and Suicides Cases -The Global Situationmentioning
confidence: 99%